Do preoperative patient-reported outcomes predict hospital length of stay for surgically-treated end-stage ankle osteoarthritis patients?. Issue 2 (February 2020) - Sutherland, Jason M.; Rajapakshe, Shan; Younger, Alastair; Crump, Trafford; Wing, Kevin; Liu, Guiping; Veljkovic, Andrea
Highlights: Patients complete patient-reported outcomes prior to AA or TAA. Preoperative patient-reported outcomes are linked with hospital data. There is no association between pre-operative PROs and hospital LOS. Discharge planning for AA and TAA may not be helped by preoperative PROs. Abstract: Background: End-stage ankle arthritis is often debilitating, associated with diminished mobility, pain, and reduced health related quality of life. Direct hospital costs of AA and TAA differ, with hospital length of stay being a major contributor. The objective of this study is to test the association between four patient-reported outcome measures with hospital length of stay, potentially important for preoperative planning and care. Methods: This study is based on a prospective cohort of patients scheduled for AA or TAA for end-stage ankle arthritis in the Vancouver Coastal Health authority, Canada. Participants completed a condition-specific instrument, the AOS, and three generic instruments, the PHQ-9, PEG and EQ-5D(3L) shortly after being scheduled for surgery. Multivariate mixed-effects Poisson regression models were used to measure the association between preoperative patient-reported outcome measures and length of stay. Results: Among the 183 patients eligible to participate, the participation rate was 48.5%. There were 89 participants. Participants reported a high level of preoperative ankle impairment and pain. The adjusted results found no relationship between the AOS, EQ-5D(3L) VAS or PHQ-9 values and participants' LOS. Participants with at least one chronic health condition and lowest SES category had longer LOS. Conclusions: This study found no evidence of an association between four PROs collected prior to AA or TAA with hospital LOS. This finding suggests collecting these PROs preoperatively may not help with discharge planning.